1993
DOI: 10.1161/01.atv.13.10.1460
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation among familial hypercholesterolemics heterozygous for either one of two Afrikaner founder LDL receptor mutations.

Abstract: Two common founder-related gene mutations that affect the low-density lipoprotein receptor (LDLR) are responsible for -80% of familial hypercholesterolemia (FH) in South African Afrikaners. The FH Afrikaner-1 (FHl) mutation (Asp^-»Glu) in exon 4 results in defective receptors with =20% of normal activity, whereas the FH Afrikaner-2 (FH2) mutation (VaUog-^Met) in exon 9 completely abolishes LDLR activity (<2% normal activity). We analyzed the contribution of these mutations and other factors on the variation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
1
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 28 publications
5
47
1
2
Order By: Relevance
“…Our results and those of others 5,8,9,11,12,15,16 suggest that identification of mutations in the LDLR gene may allow a better assessment of clinical expression in these subjects with high CHD risk. In this sense, prospective studies should be performed to evaluate further the impact of genotype on severity of FH.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our results and those of others 5,8,9,11,12,15,16 suggest that identification of mutations in the LDLR gene may allow a better assessment of clinical expression in these subjects with high CHD risk. In this sense, prospective studies should be performed to evaluate further the impact of genotype on severity of FH.…”
Section: Discussionsupporting
confidence: 71%
“…1 -4 FH shows great variability in phenotypic expression, which may be influenced by factors such as age, gender, diet, type of LDLR mutations or other genes. 5 -8 The type of LDLR gene mutation has been associated to different phenotype expression, 6,8,9 response to statins 10,11 and risk of premature CHD. 5 In Northern European FH populations, several studies have demonstrated that the type of mutation in the LDLR gene influences the FH phenotype expression.…”
Section: Introductionmentioning
confidence: 99%
“…3336 In a large study of FH patients, 33 men with CAD had significantly higher LDL cholesterol than those free of disease (7.13 versus 6.51 mmol/L), and in a recent study from South Africa, 4 FH patients with CAD had 8% higher cholesterol than those without CAD. A significant positive correlation between intimamedia thickening in the femoral artery and total serum cholesterol levels in FH patients has been reported.…”
Section: Discussionmentioning
confidence: 97%
“…The explanation for this observation is unclear but is in agreement with results from other researchers. 4 The increase in plasma cholesterol levels is approximately 0.8 mmol/L per decade in the group with the defective protein compared with approximately 0.5 mmol/L per decade in the general British population. 28 -29 In the general population a clear relation exists between the magnitude of hypercholesterolemia and the prevalence and incidence of coronary artery disease (CAD) 30 ' 31 as well as the onset of symptoms, with an increase of 1.3 mmol/L in plasma cholesterol associated with a CAD onset 10 years earlier.…”
Section: Discussionmentioning
confidence: 97%
“…The homozygous form of FH is much more severe and depending on the type of mutation may cause death in the early decades of life [1,2]. Several different factors may affect the manifestation of FH such as age, gender, diet, type of LDLR mutations and other gene mutations [3][4][5].…”
Section: Introductionmentioning
confidence: 99%